2016
DOI: 10.1155/2016/5205416
|View full text |Cite
|
Sign up to set email alerts
|

Oestrus ovisL. (Diptera: Oestridae) Induced Nasal Myiasis in a Dog from Northern Italy

Abstract: A companion dog from Milan province (northern Italy), presenting with frequent and violent sneezing, underwent rhinoscopy, laryngoscopy, and tracheoscopy procedures. During rhinoscopy, a dipteran larva was isolated from the dog and identified as first instar larval stage of O. ovis by morphological features. Reports of O. ovis in domestic carnivores are sporadic and nevertheless this infestion should be considered as a possible differential diagnosis of rhinitis in domestic carnivores living in contaminated ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…In the last 20 years, seven sporadic cases of O. ovis have been reported in humans in continental Italy, all with ocular involvement, among which a case in Perugia (Crotti et al 2005), three cases in the province of La Spezia (Dono et al 2005), a case in Ravenna's LidoAdriano (Rivasi et al 2009), one in the city of Bari (Otranto et al 2009), and another in the city of Florence (Zammarchi et al 2014). The northernmost finding of sheep bot fly larvae in Italy was a nasal myiasis in a dog from Milan (Zanzani et al 2016). The same authors reported O. ovis infestation in small ruminants from three provinces located to the north of Milan (Bergamo, Varese, and Brescia) (Zanzani et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 20 years, seven sporadic cases of O. ovis have been reported in humans in continental Italy, all with ocular involvement, among which a case in Perugia (Crotti et al 2005), three cases in the province of La Spezia (Dono et al 2005), a case in Ravenna's LidoAdriano (Rivasi et al 2009), one in the city of Bari (Otranto et al 2009), and another in the city of Florence (Zammarchi et al 2014). The northernmost finding of sheep bot fly larvae in Italy was a nasal myiasis in a dog from Milan (Zanzani et al 2016). The same authors reported O. ovis infestation in small ruminants from three provinces located to the north of Milan (Bergamo, Varese, and Brescia) (Zanzani et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The northernmost finding of sheep bot fly larvae in Italy was a nasal myiasis in a dog from Milan (Zanzani et al 2016). The same authors reported O. ovis infestation in small ruminants from three provinces located to the north of Milan (Bergamo, Varese, and Brescia) (Zanzani et al 2016). Many authors have tried to hypothesize how the spreading outside the area of center-southern Italy occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal bot fly, Oestrus ovis, causes myasis in small ruminants (1), but other casual hosts, such as humans (7) and carnivores (2)(3)(4)(5)(6)8) have also been reported. The presence of sheep nasal bot flies in Slovenia was recorded in 1997 with a seroprevalence of 40% (13).…”
Section: Discussionmentioning
confidence: 99%
“…The sheep ectoparasite, Oestrus ovis L. (Linnaeus 1758) is commonly known as nasal bot fly of sheep, goats, and other wild ruminants (1), although infestations of dogs (2,3,4,5,6), humans (7) and a cat (8) have also been documented. It has a worldwide distribution, with a preference to warmer climate, where adult flies can be active year-round (9).…”
Section: Introductionmentioning
confidence: 99%
“…Kejadian myiasis pada kulit paling sering dijumpai pada ternak dengan manifestasi klinis berupa furunkula, migrasi dan traumatika (Francesconi dan Lupi, 2012). Secara umum, jenis lalat yang menyebabkan myiasis termasuk dalam famili Calliphoridae (Stevens, 2003), Sarcophagidae (Giangaspero et al, 2017), Hypodermatidae (Pavlásek dan Minář, 2014), Oestridae (Zanzani et al, 2016) dan Gasterophilidae (Huang et al, 2016). Sedangkan jenis lalat yang menyebabkan myiasis furunkula adalah Dermatobia hominis (Meurer et al, 2016), Cordylobia anthropophaga (Fujisaki et al, 2008), Wohlfahrtia vigil (Dehghani et al, 2014), dan spesies Cuterebra (Crumley et al, 2011).…”
Section: Penyebab Myiasisunclassified